Yinchenhao Decoction Ameliorates Alpha-Naphthylisothiocyanate Induced Intrahepatic Cholestasis in Rats by Regulating Phase II Metabolic Enzymes and Transporters - Yi, Ya-Xiong; Ding, Yue; Zhang, Yong; Ma, Ning-Hui; Shi, Feng; Kang, Ping; Cai, Zhen-Zhen; Zhang, Tong (Frontiers in Pharmacology, 2018)
Yinchenhao Decoction (YCHD), a famous traditional Chinese formula, has been used for treating cholestasis for thousands of years. The cholagogic effect of YCHD has been widely reported, but its pharmacodynamic material and underlying therapeutic mechanism remain unclear. By using ultra-high-performance liquid chromatography (UHPLC)-quadrupole time-of-flight mass spectrometry, eleven original active components and eight phase II metabolites were detected in rats after oral administration of YCHD, including three new phase II metabolites. And it indicated that phase II metabolism was one of the major metabolic pathway for most active components in YCHD, which was similar to the metabolism process of bilirubin. It arouses our curiosity that whether the metabolism process of YCHD has any relationship with its cholagogic effects. So a new method for simultaneous quantitation of 8 active components and 4 phase II metabolites of rhein, emodin, genipin, and capillarisin has been developed and applied for their pharmacokinetic study in both normal and alpha-naphthylisothiocyanate (ANIT)-induced intrahepatic cholestasis rats. The results indicated the pharmacokinetic behaviors of most components of YCHD were inhibited, which was hypothesized to be related to different levels of metabolic enzymes and transporters in rat liver. So dynamic changes of intrahepatic enzyme expression in cholestasis and YCHD treated rats have been monitored by an UHPLC-tandem mass spectrometry method. The results showed expression levels of UDP-glucuronosyltransferase 1-1 (UGT1A1), organic anion-transporting polypeptide 1A4 (OATP1A4), multidrug resistance-associated protein 2 (MRP2), multidrug resistance protein 1, sodium-dependent taurocholate cotransporter, and organic anion-transporting polypeptide 1A2 were significantly inhibited in cholestasis rats, which would account for reducing the drug absorption and the metabolic process of YCHD in cholestatic rats. A high dose (12 g/kg) of YCHD remarkably increased the expression of UGT1A1, bile salt export pump, MRP2, OATP1A4 in cholestasis rats presented it exhibited the greatest ameliorative effect on cholestasis, also particularly in histopathological examination and reducing levels of alanine transaminase, aspartate transaminase, total bilirubin, direct bilirubin, and total bile acid. Considering the metabolic process of bilirubin in vivo, the choleretic effect of YCHD is proven to be related to its regulatory action on expression of metabolic enzymes and transporters in cholestatic liver.